2016
DOI: 10.1111/nhs.12316
|View full text |Cite
|
Sign up to set email alerts
|

Issues and challenges of curriculum reform to competency‐based curricula in Africa: A meta‐synthesis

Abstract: Although in recent decades reforms to undergraduate nursing and midwifery education have increasingly been guided by the concept of competency-based curriculum in a drive to produce competent graduates in the African context, the topic remains poorly researched in-depth. The related issues and challenges need to be explored in the interest of evidence-based practice. This article stems from a systematic review of qualitative literature on the design and implementation of competency-based curriculum. Data was i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 10 publications
(72 reference statements)
1
42
0
1
Order By: Relevance
“…This finding alludes to the fact that many other factors may contribute to inadequate provision of quality health care service delivery, which quite often results into high maternal and infant mortality rate (Ministry of Health, 2007;MoES, 2012). These findings are confirmed by a study done in Uganda on the factors affecting the quality of health care services (Kiguli et al, 2009) which are also consistent with those in other developing countries (Anthopoulou et al, 2017;Botma, 2014;Kadri et al, 2017;Muraraneza et al, 2017). It requires extraordinary efforts on part of stakeholders to address the perceived factors that may interfere with curriculum content implementation, to enable nurses and midwives achieve the desired outcomes.…”
Section: Appropriateness Of the Cbe Curriculumsupporting
confidence: 71%
“…This finding alludes to the fact that many other factors may contribute to inadequate provision of quality health care service delivery, which quite often results into high maternal and infant mortality rate (Ministry of Health, 2007;MoES, 2012). These findings are confirmed by a study done in Uganda on the factors affecting the quality of health care services (Kiguli et al, 2009) which are also consistent with those in other developing countries (Anthopoulou et al, 2017;Botma, 2014;Kadri et al, 2017;Muraraneza et al, 2017). It requires extraordinary efforts on part of stakeholders to address the perceived factors that may interfere with curriculum content implementation, to enable nurses and midwives achieve the desired outcomes.…”
Section: Appropriateness Of the Cbe Curriculumsupporting
confidence: 71%
“…Among the reasons for this perception is that the curricula in Turkey continuously change without any effective planning, which leads to undesirable consequences. As a support to this, in other related studies, it was found that change-based structuring studies conducted regarding the structure and implementation of curricula lead to certain problems (Akpınar, Dönder, Yıldırım, & Karahan, 2012;Handal & Herrington, 2003;Kabapınar & Karakurt, 2016;Millar, 2016;Muraraneza, Mtshali & Mukamana, 2017;Öztürk, Yalvaç-Hastürk, & Demir, 2013;Yurdakul, 2015). As mentioned by Memon (1997), a curriculum change is a complex process influenced by curriculum-based, instructional and organizational factors.…”
Section: Discussion Conclusion and Implicationsmentioning
confidence: 82%
“…Attributes of transformational leadership are important tools to achieve improved performance and can be learnt, and such leadership can further be developed through education (Duygulu & Kublay, ). It should be noted that none of the nurse managers in this study had received any formal management or leadership training and would benefit from competency‐based education and training, especially in relation to leading CQI (Solomons & Spross, ; Muraraneza et al ., ).…”
Section: Discussionmentioning
confidence: 97%